Grain size analysis of surface fluvial sediments in rivers in Kelantan, Malaysia - Wan Hanna Melini Wan Mohtar,; Siti Aminah Bassa,; Mojtaba Porhemmat, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Grain size spectrum and textural parameters for the fluvial sediment bed in seven tropical rivers of Kelantan, Malaysia are presented in this article. The samples were collected from six tributaries to the main Sungai Kelantan spanning approximately 248 km stretch of water streams. Sand or gravel dominated river was identified for each river using the sediment composition analysis. Textural pattern shows complicated profiles of mean size and no consistent decreasing grain size and gradation parameter were observed towards the downstream flow. Most of the samples fall under the category of either very poorly sorted or poorly sorted and has very platykurtic kurtosis distributions. CM diagram (C=one percentile in microns and M = median grain size in microns) suggested that the deposition of fine-grained sediment for samples with median grain size d50 <1 mm are either by rolling, rolling and saltation or saltation and suspension.